Social jetlag affects subjective daytime sleepiness in school-aged children and adolescents: A study using the Japanese version of the Pediatric Daytime Sleepiness Scale (PDSS-J). (25th November 2016) - Komada, Yoko; Breugelmans, Raoul; Drake, Christopher L.; Nakajima, Shun; Tamura, Norihisa; Tanaka, Hideki; Inoue, Shigeru; Inoue, Yuichi
ABSTRACT: The aim of this study was to elucidate the level of daytime sleepiness in Japanese school-aged children and adolescents, and to examine associated factors including sleep loss and social jetlag using the Japanese version of the Pediatric Daytime Sleepiness Scale (PDSS-J). After the linguistic validation of the PDSS-J with a multi-step translation methodology, consisting of forward translation, back translation, expert review and cognitive debriefing interviews, we conducted a psychometric validation for 492 students aged 11–16 years (46.7% boys) of public elementary school, junior high school and high school, using the PDSS-J, the Karolinska Sleepiness Scale (KSS), and bedtimes and wake-up times on school days and free days. Internal consistency (Cronbach's alpha) of the PDSS-J was 0.77, and the test–retest reliability demonstrated by the intraclass coefficient was 0.88. Multivariate logistic regression analysis revealed that both short sleep duration and social jetlag were identified as factors associated with daytime sleepiness, after adjustment for age and sex. PDSS-J scores were significantly higher in the group with large social jetlag with or without sufficient sleep duration than in the group with sufficient sleep duration and small social jetlag. The PDSS-J is an important tool for assessing daytime sleepiness, given its ease of administration and robust psychometric properties. The impact of not only sleep loss but also social jetlag on daytime sleepiness among school-aged children and adolescents must be fully taken into account.